Prognostic Value of P-POSSUM and Osteopenia for Predicting Mortality After Emergency Laparotomy in Geriatric Patients - Ah, Rebecka (Bull Emerg Trauma, 2019)
OBJECTIVE: To evaluate the Portsmouth-Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity (P-POSSUM) in comparison with other risk factors for mortality including osteopenia as an indicator for frailty in geriatric patients subjected to emergency laparotomy. METHODS: All geriatric patients (≥65 years) undergoing emergency laparotomy at a single university hospital between 1/2015 and 12/2016 were included in this cohort study. Demographics and outcomes were retrospectively collected from medical records. Association between prognostic markers and 30-day mortality was assessed using Poisson and backward stepwise regression models. Prognostic value was assessed using receiver operating characteristic (ROC) curves. RESULTS: 209 patients were included with a mean age of 76 ± 7.3 years. American Society of Anesthesiologists (ASA) classification, age, indication and type of surgery, hypotension, transfusion requirement and current malignancy proved to be statistically significant predictors of 30-day mortality. P-POSSUM mortality was statistically significant in the backward stepwise regression (incidence rate ratio=1.58, 95% CI: 1.16–2.15, p=0.004) while osteopenia was not. P-POSSUM had poor prognostic value for 30-day mortality with an area under the ROC curve (AUC) of 0.59. The prognostic value of P-POSSUM improved significantly when adjusting for patient covariates (AUC=0.83). CONCLUSION: P-POSSUM and osteopenia alone hardly predict 30-day mortality in geriatric patients following emergency laparotomy. P-POSSUM adjusted for other patient covariates improves the prediction.